USE OF RHIZOBIUM AS A BIOFERTILIZER FOR PLANTS: PEMANFAATAN RHIZOBIUM SEBAGAI BIOFERTILIZER BAGI TANAMAN - Zulfida, Ida (UPMI Proceeding Series, 2023)
Nitrogen (N2) is an essential element for living things, especially plants. The element nitrogen is one of the components that make up protein and plays a role in the process of photosynthesis. The nitrogen content in the atmosphere is very abundant, which is around 78%, but the nitrogen is in the form of molecules which are mostly unreactive, so it cannot be absorbed directly by plants. Therefore, it is necessary to transform nitrogen in the air into a molecular form that can be absorbed by plants. Nitrogen can only be absorbed by plants (NH4+) in the form of ammonium ions or nitrate ions (NO3+). Dinitrogen gas from the atmosphere is converted into ammonia (NH3), then fixed in the soil through a fixation process.